The benefits and risks of adding PD-1/PD-L1 inhibitors to chemotherapy for stage IIIb-IV non-small-cell lung cancer: an updated meta-analysis based on phase 3 randomized controlled trials - Xu, Yun; Zhong, Baoliang; Yu, Chunlin; Hou, Qingjian; Chen, Wenying; Zheng, Wen; Zhang, Wenxiong; Zhou, Tonggang (Frontiers in Oncology, 2025)
BackgroundPrevious research has confirmed that integrating PD-1/PD-L1 inhibitors with chemotherapy (PC) represents a more effective strategy for treating advanced non-small-cell lung cancer (NSCLC). However, with the increasing number of phase 3 randomized controlled trials (RCTs) published in recent years, it is essential to re-evaluate the validity of this conclusion and to comprehensively assess the efficacy and safety across diverse patient subgroups.MethodsWe systematically reviewed phase 3 RCTs comparing PC with chemotherapy alone for stage IIIb-IV NSCLC. Data were extracted and analyzed for overall survival (OS), progression-free survival (PFS), response rates, and adverse events (AEs). Subgroup analyses were performed based on factors such as disease stage, pathological type, etc.ResultsAfter screening, 19 phase 3 RCTs involving 9335 patients were included. Our updated analysis confirmed at PC therapy significantly improves OS (hazard ratio [HR]: 0.73 [0.69, 0.77], P < 0.00001), PFS (HR: 0.56 [0.52, 0.60], P < 0.00001), duration of response (DOR, HR: 0.50 [0.45, 0.54], P < 0.00001) and objective response rate (ORR, risk ratio [RR]: 1.59 [1.51, 1.67], P < 0.00001) compared to chemotherapy alone. The survival benefits were consistent across all subgroups and increases with longer follow-up. Brain metastases and PD-L1 combined positive score (CPS) > 50% were the favorable factors for PC group. However, the combined treatment was associated with an increased incidence of total/grade 3–5 treatment emergent AEs (TEAEs), and immune-related AEs (irAEs), although the overall safety profile remained manageable. The most common AEs in the PC group were blood toxicity related AEs (anemia, neutrophil count decreased, etc).ConclusionThe PC therapy continues to provide a substantial survival benefit for patients with stage IIIb-IV NSCLC. However, its higher incidence of AEs, especially irAEs, needs to be taken seriously.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251005925, identifier CRD420251005925.